Studi Eksperimental Pengaruh Perbedaan Sudut Kemiringan Terhadap Temperatur Onset Termoakustik Generator Gelombang Berdiri - Agistya Anugrah, Rinasa (Universitas Muhammadiyah Yogyakarta, 2019)
Thermoacoustic generator ia one of energy conversion device that change thermal energy to acoustic form energy. This device can get many beneficial of thermal energy which banned and not be used again from industry, devices of the hospitals, geothermal, and solar energy. The device consist or two type, standing wave and traveling wave. In the research used a standing wave thermoacoustic generator because of the cost is relatively cheaper and the construction is easy to set than traveling wave type. Onset temperature is one of the most important parameter in thermoacoustic generator to be researched. In that aplication, onset temperature can representated how many the performance of this device, if seen by input energy used the system of the thermoacustic generator. Decreasing onset temperature could make decrease of thermal energy used to generator. Beside stack and resonator length, the other parameter that more important to research is tilted angles. In this researched would be done researched with variation of tilted angles -90º, 0º, dan 90º. It would be found the effective tilted angle used, the performance was presented by the least onset temperature. The result was the tilted angle decreased when the onset temperature decreased too. If seen by the input energy, the best performance of thermoacoustic generator is on 90o tilted angle.